The characteristics of a new product through user knowledge in the early stage of a design process - Taha, Zahari; Alli, Hasan; Abdul Rashid, Salwa Hanim (Trans Tech Publications, 2013)
User knowledge has become a performance indicator that determines the success of a business. It provides a valuable source of information for product developer to develop the specification and characteristics of a new product. Various methods have been studied to extract and integrate the user knowledge during the early stage of a design process. This paper focuses the relation between the success of a product and the product specification. Interviews with product designers were conducted. The results of this study provide a foundation for product developers to specify the product characteristics. The strategies, information and knowledge for a structured approach to product characteristics can then be developed.